Efficacy and Cardiovascular Safety of GLP-1 Receptor Analogues - Iqbal, Anoop M.; Imamudeen, Nasvin; Basheer, Amjad; Menon, Sukrita; Mohan, Gisha; Sani, Tesil Nedumkallel; Haroon, Nisha Nigil (Current Drug Safety, 2021)
Glucagon-like peptide- 1 receptor analogs (GLP-1RAs) are incretin mimetics with potent glucose-dependent insulinotropic action that translates to glycemic control in people with type- -2 diabetes mellitus (T2DM). These agents potentially have the ability to stimulate proliferation or prevent apoptosis of pancreatic β-cells, induce weight-loss and provide vascular benefits in patients with T2DM. Newer GLP-1RA, semaglutide has shown a robust reduction in HbA1c up to 1.5 - 1.8%. However, individual differences exist between the different GLP-1RAs, in terms of efficacy, pharmacokinetics, tolerability, and vascular protection. The potential of vascular protection offered by newer anti-diabetic agents has generated a lot of excitement in the field of diabetes, and to a large extent, is now driving treatment decisions. So far, six cardiovascular outcome trials of GLP-1 RAs have been published, analyzing lixisenatide (ELIXA), liraglutide (LEADER), semaglutide (SUSTAIN-6), long-acting exenatide (EXSCEL), dulaglutide (REWIND), and oral semaglutide (PIONEER 6) with a follow-up duration of 2-4 years. LEADER, REWIND and SUSTAIN-6 trials have demonstrated a reduction in rates of major adverse cardiovascular events with active GLP-1 RA treatment, but ELIXA, PIONEER 6 and EXSCEL, have been neutral. In this review, we discuss the available evidence from randomized controlled trials (RCTs) analyzing the cardiovascular effects of various GLP-1 RAs with the aim of comparing individual drugs. We have also summarized the general aspects of GLP-1RAs that can be applied in clinical practice.
Keywords: cardiovascular disease